Pelléas et Mélisande drame lyrique en cinq actes et douze tableaux - Debussy, Claude 1862-1918 (Deutsche Grammophon, 2002)
Thanks to his work with the German stage director Peter Stein, who had already produced the Verdi operas "Otello" and "Falstaff" in Cardiff, Boulez was able to count on a like-minded artist who would help him open new dimensions, particularly since this opera demands meticulous acting from the singers. Their production, with stage settings by Karl-Ernst Herrmann, ranks among the most successful productions in the history of this opera. It was recorded under studio conditions at Cardiff's New Theatre in 1992. [www.unitel.de]
Keywords: DVD-Video